2001
DOI: 10.1007/bf02234398
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening cytomegalovirus colitis in the immunocompetent patient

Abstract: Cytomegalovirus colitis in the immunocompetent patient is an unusual clinical entity. We describe a patient with life-threatening cytomegalovirus colitis in the absence of immune deficiency and review the medical literature available on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
1
26
1
9
Order By: Relevance
“…Symptomatic CMV infections are typically manifested as a non-specific febrile disease or a mild self-limiting mononucleosis-like syndrome [4]. However, there are many reports of severe or prolonged symptomatic CMV infection in immunocompetent patients [5][6][7]. After primary infection, CMV establishes a lifelong latent infection that can periodically reactivate [3].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic CMV infections are typically manifested as a non-specific febrile disease or a mild self-limiting mononucleosis-like syndrome [4]. However, there are many reports of severe or prolonged symptomatic CMV infection in immunocompetent patients [5][6][7]. After primary infection, CMV establishes a lifelong latent infection that can periodically reactivate [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this group, 47% of them presented conditions that induced alterations of the immune system, such as pregnancy, renal failure, diabetes mellitus or untreated cancer (non-hematologic) (9). Another review with 44 patients with CMV colitis showed an average age of 63 years (11).…”
Section: Discussionmentioning
confidence: 97%
“…Em artigo recente de metanálise, no período de 1980 a 2003, somente 44 casos foram identificados. Entre estes, 16 pacientes tiveram co-morbidades com alterações imunes, o que significa somente 28 casos CMV em pacientes com sistemas imunes íntegros (13) .…”
Section: Discussionunclassified
“…A maioria dos pacientes identificados tinha mais que 55 anos de idade, com uma idade média de 61,1 anos, isto poderia ser conseqüência de um enfraquecimento do sistema imune, decorrente do envelhecimento (13) . Com respeito à infecção pelo CMV, habitualmente a infecção ocorre durante a infância ou em adultos jovens.…”
Section: Discussionunclassified